Investigation of the Road Noise Source Employing an Automatic Noise Monitoring Station - SZCZODRAK, Maciej; CZYŻEWSKI, Andrzej; KOTUS, Józef (Archives of Acoustics, 2008)
The paper presents a pilot investigation of noise source models in two selected localizationsin the context of future dynamic noise map creation. The experiments were carried out usingthe automatic noise monitoring station engineered at the Multimedia Systems Departmentof the Gda´nsk University of Technology. The results of the noise measurements employingmonitoring stations and its comparison to the reference values are depicted. Short- and longtermstudies of noise level are also presented. The experiments described include a comparisonbetween environmental measurement results and the noise level prediction results. Dataobtained from the NMPB-96 (Nouvelle Méthode de Prévision du Bruit) and the Harmonoisemodel data provide the subject of the analysis. The proposed solution of permanent noisemonitoring system is also shortly described.